The NKI Internet College: A Review Of 15 Years Delivery Of 10,000 Online Courses - Paulsen, Morten; Rekkedal, Torstein (International Review of Research in Open and Distributed Learning, 2001)
This article presents NKI's experiences with online education from the time the idea was conceived in 1985 to the point when the total number of course enrolments exceeded 10,000 in June 2000. The 15 year period covers three generations. The first generation (1985-1994) was characterised by system development and experimentation with emerging technology. The second generation (1994-96) was a period of transition from the EKKO computer conferencing system, which NKI developed for online education, to Internet systems with text-based user interfaces. The third generation, 1996 to the present, began with the introduction of graphic user interfaces and the World Wide Web (WWW) and is characterised by a vigorous expansion and the introduction of large-scale online education.